PELATIHAN PEMANFAATAN MEDIA INTERNET DENGAN MENGGUNAKAN APLIKASI GOOGLE UNTUK PONDOK PESANTREN MA’HAD AR-RIDHA KLATEN - Prasetyo, Hendro Joko; Lutfiyani, Rizka Safitri (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2023)
Advances in technology in the 4.0 era are inseparable from the level of education mastered. The higher the education achieved, the easier it will be to create modern technology that is beneficial to human life. Therefore, the role of educational institutions as a place that creates educated personnel is very vital. This includes educational institutions such as Islamic boarding schools, which in this modern era need a touch of technology. Ma'Had Ar-Ridha Klaten Islamic Boarding School, this Islamic boarding school is specifically for students who want to become hafidz of the Koran and preachers who come from orphans and the poor. At the free Ma'Had Ar-Ridha Klaten Islamic Boarding School, the students are taught religious material and the Koran. But the introduction to technology and computers is still very limited. This community service is carried out by the Informatics Management of Vocational Program at Widya Dharma Klaten University to help students at Ma'Had Ar-Ridha Klaten Islamic Boarding School, so they can use computers and Google applications to help or support them in carrying out its activities.